THE IMPLEMENTATION OF ACTION LEARNING STRATEGY TOWARD STUDENTS’ CARACTER BUILDING IN BIOLOGY LEARNING PROCESS - Joko Ariyanto, Irfana Fauziah, Meti Indrowati (P Biologi FKIP UNS Surakarta, 2015)
This research aims to find out the extent of character building differences (care, smart, dependent, and responsible) between the control group and Action Learning treated group.This research is quasi experiment in nature using the Non-equivalent Control Group Design. This research used Action Learning method applied in experiment group and conventional method (discussion, presentation, and exchange of ideas) in control group. The participant of this research was all students of grade VIII SMP Negeri 5 Surakarta 2012/2013. The sampling technique used was cluster sampling. As a result, VIII class participated as the experiment group and VIIIH participated as the control group. The data was collected using questionnaire, check point test, observation, and character rubric. Anacova was used to test the hypothesis with the covariant pre-test.The conclusion of this research is there are differences students? character building (care, smart, dependent, and responsible) between the control group with Action Learning treated group. Keywords: Action Learning strategy, character education, character